Jedan lirski element u romanu Zlatni zmaj Dežea Kostolanjija, sagledan iz prevodilačke perspektive (Philologia, 2021)
The great classic of modern Hungarian literature, Dezső Kosztolányi (1885 – 1936), a prolific poet in the first place, has put a significant emphasis on the sophisticated elaboration of linguistic expressions in his prose writings as well. These linguistic, stylistic features play a crucial role in certain points of Kosztolányi’s novels in the thematic and existential sense. This paper attempts to point out to a momentum of this kind in one of Kosztolányi’s novels, Aranysárkány (The Golden Kite). The narrator employs a rhyme in the most dramatic moment of Antal Novák’s suicide, adding a special, irony-loaded quality to the unspeakable dreadful violent moment of death, which is rarely touched upon in literature. From the perspective of the text-oriented reader, the translation of this specific part of the text is crucial, since the reader needs to become aware of the linguistic and stylistic emphasis of this specific segment of the text.
Keywords: textual ('narrow') reading; emphasized momentum; prose rhyme; translation difficulties